Sri Lanka : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2002)
This report evaluates the Observance of Standards and Codes on Fiscal Transparency for Sri Lanka. Sri Lanka has achieved a substantial degree of fiscal transparency in several important areas, including the legal and administrative framework for fiscal management, the compilation and publication of detailed accounts for the central government, and the maintenance of separate and aggregate accounts for public corporations. The government is also undertaking additional reforms to improve transparency, including the passage of a new Public Finance Act, and the development of a quantitative macroeconomic framework for budget preparation.